Hubungan Kedisiplinan Siswa dengan Hasil Belajar Akidah Akhlak di MTSN Kota Bogor Tahun 2023 - Elywarni, Elywarni; Maemunah Sa’diyah, Maemunah Sa’diyah; Noor Isna Alfaien, Noor Isna Alfaien (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study aims to describe the relationship between student discipline and learning outcomes in Akidah Akhlak class VIII at MTsN Kota Bogor. The method used in this research is quantitative with a correlation approach. The sample in this study amounted to 78 respondents with simple random sampling technique. Data collection using questionnaires distributed to respondents and leger documentation of student learning outcomes. The results of the questionnaire validity test for the student discipline variable with a total of 15 items showed overall valid results and the reliability test with a result of 0.805 means reliable. The data analysis carried out is to describe and make a category table of each variable, then to see the relationship using product moment correlation. Based on the data obtained, student discipline shows a moderate category level with a total of 52 students with a percentage value of 66.7% and learning outcomes there are 52 students with a percentage value of 66.7% having scores in the moderate category range. The correlation test results show a number of 0.307> 0.05, which means that there is a significant positive relationship between student discipline and learning outcomes in Akidah Akhlak subjects. The results of hypothesis testing by comparing rcount with rtable show the results of 0.307>0.2227 then the alternative hypothesis is accepted (Ha), based on these data is that there is a significant relationship between student discipline and student learning outcomes at MTsN Kota Bogor.